Cost-effectiveness of agriculture risk management strategies for resilience to climate shocks in Niger State, Nigeria - Olufemi Adekunle, Adedayo (2022)
The ability of a system, community or society exposed to hazards to resist, absorb, to accommodate and recover from the effects of a hazard in a timely and efficient manner is termed resilience. In this study we used a recent cross-sectional survey data of 293 farming households in Niger State, Nigeria to examine the cost effectiveness of risk management strategies for resilience to climate shocks. Benefit-cost analysis of mitigation strategies was examined where benefit-cost ratio (BCR), and net present value (NPV) were used as decision rules. The mitigation strategies mostly used were drought tolerant crops (62.8 %), crop diversification (60.8 %), buffer stock (54.6 %) and dry season farming (41.3 %). The result showed that about 52 % of the sampled households were food secure while 48 % of them were food insecure. The result showed that dry season rice farming had the highest net benefit (NB) and NPV ($ 199.98) while rain fed maize ($ 35.01) and rice had the least NPV; the result showed the NPV for drought tolerant crops- cassava ($ 170.25), millets ($ 101.58) and sorghum ($ 96.43). The study recommends that households should take up dry season rice farming and grow drought tolerant crops such as cassava, millets and sorghum. Governments should invest in and research and breeding of drought tolerant crops in order to improve food security and household resilience.